2017
DOI: 10.1051/matecconf/201713500039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Welding Speed on Microstructure and Mechanical Properties due to The Deposition of Reinforcements on Friction Stir Welded Dissimilar Aluminium Alloys

Abstract: The strength of the welded joint obtained by solid state stir welding process was found to be improved as compared to fusion welding process. The deposition of reinforcements during friction stir welding process can further enhance the strength of the welded joint by locking the movement of grain boundaries. In the present study, the aluminium alloys AA2024 and AA7075 were welded effectively by depositing the multi-walled carbon nanotubes in to the stir zone. The mechanical properties and microstructures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The mechanical characteristics of the material are enhanced by producing the groove on the BM (Baridula et al , 2016) and then reinforced with composites and processed with FSP (Yuvaraj et al , 2015). When the groove width increases, FSPed zone or surface composite area is reduced as shown in Figure 4 (Rathee et al , 2017b; Baridula et al , 2018).…”
Section: Process Parametersmentioning
confidence: 99%
“…The mechanical characteristics of the material are enhanced by producing the groove on the BM (Baridula et al , 2016) and then reinforced with composites and processed with FSP (Yuvaraj et al , 2015). When the groove width increases, FSPed zone or surface composite area is reduced as shown in Figure 4 (Rathee et al , 2017b; Baridula et al , 2018).…”
Section: Process Parametersmentioning
confidence: 99%
“…Past works have revealed that groove size plays a significant role in enhancing reinforced weld joint quality. For example, Ravinder et al [9] investigated the effect of varying groove size (width) on the joint strength of SiC-reinforced AA 5053-AA6061 dissimilar friction stir welded joint. It was established that varying the groove size influences the mechanical properties of the welded joint due to the variation of reinforcement's content at different groove widths.…”
Section: Introductionmentioning
confidence: 99%